2001
DOI: 10.1042/cs20000123
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of resveratrol-induced vasorelaxation differs in the mesenteric resistance arteries of lean and obese rats

Abstract: Resveratrol has been shown to induce vasorelaxation. In this study, we investigated the mechanism(s) of resveratrol-induced vasorelaxation in resistance mesenteric arteries from male lean and dietary-induced obese rats. Compared with lean rats, arteries from dietary-obese rats showed significant (P<0.001) endothelial dysfunction, as indicated by a decrease (>20%) in maximal acetylcholine-induced vasorelaxation. Resveratrol (5-35 micromol/l) induced concentration-dependent relaxation of mesenteric arteries prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…To assess the endothelial integrity of the preparation, we used acetylcholine (20 μM). Failure of arteries to relax to acetylcholine was considered to indicate a state of endothelial denudation (22).…”
Section: Assessment Of Vascular Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the endothelial integrity of the preparation, we used acetylcholine (20 μM). Failure of arteries to relax to acetylcholine was considered to indicate a state of endothelial denudation (22).…”
Section: Assessment Of Vascular Functionmentioning
confidence: 99%
“…The resveratrol-induced vasorelaxation may either be endothelium-dependent (attenuated by L-NAME) or endothelium-independent (6,7,10). The mechanism of endothelium-independent vasorelaxation induced by resveratrol is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the endothelial integrity of the preparation we have used acetylcholine (20 µM). Failure of arteries to relax to acetylcholine was considered to indicate a state of endothelial denudation (6).…”
Section: Assessment Of Vascular Functionmentioning
confidence: 99%
“…It has been shown that resveratrol exhibits the estrogenic [30], antioxidant [31], antiviral [32], antiplatelet [33], anti-thyroid [34] and cancer chemopreventive activity [35]. Furthermore, resveratrol enhances the expression and activity of endothelial nitric oxide synthase [36] and induces vasorelaxation [37]. Resveratrol has the inhibitory effect on enzyme α-glucosidase which can be a potential mechanism of its antidiabetic activity [38].…”
Section: Resorcinol Derivativesmentioning
confidence: 99%